Construction of embedded online teaching platform based on AES-RSA encryption algorithm - Xiaojing Kong; Guanli Yue (Discover Artificial Intelligence)
Abstract With the development of economy, people's demand for high-quality and diversified educational resources increases. However, under the frequent occurrence of network attacks, data leakage and other events, network security and information security need to be solved urgently by the current online teaching platform. To this end, the research adopts Advanced Encryption Standard encryption algorithm and introduces Rivest-Shamir-Adleman to improve it, and applies it to construct an embedded online teaching platform, aiming to ensure user’s personal information security. Experimentally, the decryption speed of the Advanced Encryption Standard-Rivest-Shamir-Adleman encryption algorithm stays around 100 ms when the number of bytes is below 60. When file size increasing, the encryption time of the proposed algorithm increases minimally. Also, the key generation time of the algorithm is always less than 1500 ms, and the average time taken to defend the online teaching platform against brute force attacks can be up to 232.1 ms. In addition, the research algorithm has the best scalability, the platform obfuscation is better, and the platform always has the lowest ciphertext bit count. In conclusion, it can be seen that the embedded online teaching platform of the study has the best confidentiality of user information, which guarantees the confidentiality and integrity of learners' personal information and teaching resources. Strong encryption technology provides solid security for the application of online education platforms, allowing educational innovation to take place in a more secure and controlled environment.